2020
DOI: 10.1016/j.apm.2020.01.046
|View full text |Cite
|
Sign up to set email alerts
|

The continuous resupply policy for deteriorating items with stock-dependent observable demand in a two-warehouse and two-echelon supply chain

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…This study has significant theoretical implications in emerging renewable energy implementation and stock-dependence strategy in sustainable supply chain literature. In practice, organizations believe that displaying a greater quantity of products (such as flowers or vegetables) increases market demand (Zhou and Yang 2005;Ghiami et al, 2020). However, it is observed that the high rate of green technology investment is a severe challenge for organizations to reduce CO2 emission, which increases the overall cost significantly.…”
Section: Theoretical Implicationmentioning
confidence: 99%
See 1 more Smart Citation
“…This study has significant theoretical implications in emerging renewable energy implementation and stock-dependence strategy in sustainable supply chain literature. In practice, organizations believe that displaying a greater quantity of products (such as flowers or vegetables) increases market demand (Zhou and Yang 2005;Ghiami et al, 2020). However, it is observed that the high rate of green technology investment is a severe challenge for organizations to reduce CO2 emission, which increases the overall cost significantly.…”
Section: Theoretical Implicationmentioning
confidence: 99%
“…Further, demand also plays an important role in market expansion since it depends on many factors, including price, quality, guarantee, advertising, a sales promotion campaign, etc. In addition to this, it has also been found that displaying a greater quantity of a product(such as flowers or vegetables) tends to attract more customers (Zhou and Yang 2005;Ghiami et al, 2020). This fact has attracted the attention of many researchers, and they have incorporated stock-dependence criteria into their demand (You and Hsieh 2007;Bardhan et al, 2019;Wen et al, 2019) while designing cost function.…”
Section: Introductionmentioning
confidence: 99%
“…The general formula was better than the conventional EOQ inventory model in which demand depends on stock. Continuous resupply for deteriorating items applies to a firm's net present value for its future cash flow [16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Khan et al [38] developed a TWI model for aging goods with an automated payment system using all these collaboration ideas. Ghiamia and Beullens [39] examined stock-dependent demand in the case of declining goods for a retailer with TWI, where the retailer attempts to achieve the optimum integrated procurement strategy by cooperation with a supplier. The advantages of both the continuous resupply approach and the widely used approach have been established in the OW and RW literature.…”
Section: Literature Reviewmentioning
confidence: 99%